MOST RECENT FINDINGS IN EARNINGS MANAGEMENT AREA: INTERESTING INSIGHTS FROM TRADITIONALLY TOP 5 LEADING ACCOUNTING JOURNALS - CUZDRIOREAN, Dan Dacian (Annales Universitatis Apulensis Series Oeconomica; Vol 2 No 15 (2013): Annales Universitatis Apulensis Series Oeconomica, 2013)
A meta-analysis was conducted over the last 5 years comprising traditionally top 5 leading accounting research. The paper overviews emerging research and identify both framework papers that attracted significant attention and leading scholars in the field. The earnings management area exhibits considerable momentum, found largely driven by North American scholars focused research groups. The main goal of the paper was to offer a thoroughly understanding of what literature has achieved so far and to identify further research trends that scholars can use. In this respect present study can guide researchers, but also given the economic implications of the earnings management activities, our audience can comprise as well practitioners, accounting regulators or managers. Conclusions are developed based on the sample assessed.